Determinants of EFL learning success in content and language integrated learning. Issue 1 (2nd January 2022) - Goris, José; Denessen, Eddie; Verhoeven, Ludo
ABSTRACT: The present study investigates whether CLIL learners' high scores in English as a foreign language (EFL) can be attributed to three specific learner variables: 'EFL aptitude', 'EFL confidence' and 'international orientation' – and whether out-of-school EFL exposure has an effect. The study was undertaken in eight secondary school CLIL classes in four European countries: the Netherlands, Germany, Italy and Hungary. The results showed a number of significant effects, both initially and after two years. In particular, learners' EFL confidence was found to have a stronger influence on L2 proficiency results than either EFL aptitude, involvement in the international world or the presence of English in society at large.